2008
DOI: 10.1093/aob/mcn215
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits as indicators of fodder provision over a short time scale in species-rich grasslands

Abstract: The PFT composition and the Ni were more reliable than the plant functional traits measured in the field for evaluating herbage growth pattern and digestibility in spring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 51 publications
(52 reference statements)
3
45
0
2
Order By: Relevance
“…; Ansquer et al . ; Schumacher & Roscher ; Lavorel et al . ; Minden & Kleyer ; Laliberté & Tylianakis ; Lienin & Kleyer ).…”
Section: Discussionunclassified
“…; Ansquer et al . ; Schumacher & Roscher ; Lavorel et al . ; Minden & Kleyer ; Laliberté & Tylianakis ; Lienin & Kleyer ).…”
Section: Discussionunclassified
“…Timing of first use can impact significantly forage quality according to the relative abundances of grass functional types (Ansquer et al 2009). O'Donovan et al (2004 as well as Kennedy et al (2006) showed some positive effects of early and late grazing to improve forage quality for livestock.…”
Section: Parcel and Farm Scales: Two Complementary Scales For Ei Of Mmentioning
confidence: 99%
“…Ansquer et al . () found a negative relationship between digestibility and the proportion of a plant functional type consisting in stress‐tolerant species with high leaf dry matter content, calculated for grasses in 18 grassland plots, while Andueza et al . () found a negative relationship between CWM of leaf dry matter content and digestibility in a comparison of two meadows differing in management intensity.…”
Section: Introductionmentioning
confidence: 96%
“…() and Ansquer et al . () showed that grasslands with a high proportion of grasses with low leaf dry matter content had a higher digestibility than grasslands dominated by grasses with a high leaf dry matter content. A more formal test of the dominance hypothesis requires the analyses of relationships between community‐weighted means of traits (CWM: the product of the mean trait value of a species by its relative abundance in the community, Garnier et al .…”
Section: Introductionmentioning
confidence: 99%